Ribociclib-induced liver injury: a case report - Schaeffer, Sofia; Lutz, Christian; Dobbie, Michael; Terracciano, Luigi M.; Matter, Matthias; Vosbeck, Jürg; Heim, Markus H.; Bernsmeier, Christine (Frontiers in Oncology, 2023)
Background Idiosyncratic drug-induced liver injury (DILI) is a rare, unpredictable hepatic adverse event and the most common cause of acute liver failure in Europe and the US. Ribociclib is a potent Cyclin-dependent kinase 4 and 6 (CDK4/6)-inhibitor administered for advanced hormone-receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative breast cancer. Previous reports have shown hepatotoxicity without liver necrosis related to ribociclib. Case presentation A 41-year-old female patient with primary metastatic HR-positive, HER2-negative breast cancer developed liver enzyme elevation under treatment with ribociclib. Ribociclib was withdrawn 8 weeks after initiation due to liver enzyme elevation. A liver biopsy, performed due to further enzyme increase (peak ALT 2836 U/l), onset of jaundice (peak bilirubin 353 µmol/l) and coagulopathy (INR 1.8) two weeks later, revealed acute hepatitis with 30% parenchymal necrosis. Roussel Uclaf Causality Assessment Method (RUCAM) score was 7 points (probable). Under treatment with prednisone (60mg), initiated 2 weeks after drug withdrawal, and subsequently N-acetylcysteine (Prescott regimen) liver enzymes normalized within 8 weeks along with prednisone tapering. Conclusion This case illustrates the development of a severe idiosyncratic hepatocellular pattern DILI grade 3 (International DILI Expert Working Group) induced by ribociclib. Routine liver enzyme testing during therapy, immediate hepatologic work-up and treatment interruption in case of liver enzyme elevation are highly recommended. Corticosteroid treatment should be considered in cases of severe necroinflammation.